Paramedic Attitudes and Experiences Working as a Community Paramedic - Paramalingam, Aarani; Ziesmann, Andrea; Pirrie, Melissa; Marzanek, Francine; Angeles, Ricardo; Agarwal, Gina; Brar, Jasdeep; Koester, Christie; Mahal, Guneet; Plishka, Mikayla (My University, 2024)
Background Community paramedicine (CP) is an extension of the traditional paramedic role, where paramedics provide non-acute care to patients in non-emergent conditions. Due to its success in reducing burden on hospital systems and improving patient outcomes, this type of paramedic role is being increasingly implemented within communities and health systems across Ontario. Previous literature has focused on the patient experience with CP programs, but there is lack of research on the paramedic perspective in this role. This paper aims to understand the perspectives and experiences, both positive and negative, of paramedics working in a CP program towards the community paramedic role. Methods An online survey was distributed through multiple communication channels (e.g. professional organizations, paramedic services, social media) and convenience sampling was used. Five open-ended questions asked paramedics about their perceptions and experiences with the CP role; the survey also collected demographic data. While the full survey was open to all paramedics, only those who had experience in a CP role were included in the current study. The data was qualitatively analyzed using a comparative thematic analysis. Results Data was collected from 79 respondents who had worked in a CP program. Three overarching themes, with multiple sub-themes, were identified. The first theme was that CP programs fill important gaps in the healthcare system. The second was that they provide paramedics with an opportunity for lateral career movement in a role where they can have deeper patient connections. The third was that CP has created a paradigm shift within paramedicine, extending the traditional scope of the practice. While paramedics largely reported positive experiences, there were some negative perceptions regarding the slower pace of work and the “soft skills” required in the role that vary from the traditional paramedic identity. Conclusions CP programs utilize paramedic skills to fill a gap in the healthcare system, can improve paramedic mental health, and also provide a new pathway for paramedic careers. As a new role, there are some challenges that CP program planners should take into consideration, such as additional training needs and the varying perceptions of CP.
An infographic presenting the results of the following publication: Paramalingam, A., Ziesmann, A., Pirrie, M. et al. Paramedic attitudes and experiences working as a community paramedic: a qualitative survey. BMC Emerg Med 24, 50 (2024). https://doi.org/10.1186/s12873-024-00972-5
Keywords: Community Paramedicine; Paramedic; Vulnerable Populations